Comment on 'The distribution of antibiotic use and its association with antibiotic resistance' - Pouwels, K; Butler, C; Robotham, J (eLife Sciences Publications, 2019)
We are writing to comment on the recent study by Olesen et al., 2018 on antibiotic use and antibiotic resistance.